Penerapan Teknik Sinematografi oleh Director of Photography Pada Produksi Video Feature “Penjaga Napas Seni Wayang Golek” - Sulistiani, Iis; Sugito, Toto; Mahameruaji, Jimi Narotama (Innovative: Journal Of Social Science Research, 2025)
As the Director of Photography in the production of the video feature “Penjaga Napas Seni Wayang Golek”, the author is responsible for all elements related to the visual aspects of this work. This research aims to analyze the application of cinematography techniques, namely camera angle, camera movement, shot size, image composition, and lighting in making video features. The method used focuses on the implementation of qualitative descriptions with data collection techniques through observation and literature study. The results of these findings show that the application of good cinematographic techniques will produce visuals that are interesting and not monotonous so that they can strengthen the message to be conveyed from a work. This video feature is expected to show that wayang golek is not just an art performance, but also a cultural heritage that has high historical value and needs to be preserved. By using interesting cinematography techniques and evocative narration, this video feature is expected to increase public awareness, especially the younger generation, about the importance of preserving traditional arts.